The single-sided pulsator CO Camelopardalis. Issue 4 (13th April 2020) - Kurtz, D W; Handler, G; Rappaport, S A; Saio, H; Fuller, J; Jacobs, T; Schmitt, A; Jones, D; Vanderburg, A; LaCourse, D; Nelson, L; Kahraman Aliçavuş, F; et al.
ABSTRACT: CO Cam (TIC 160268882) is the second 'single-sided pulsator' to be discovered. These are stars where one hemisphere pulsates with a significantly higher amplitude than the other side of the star. CO Cam is a binary star comprised of an Am δ Sct primary star with T eff  = 7070 ± 150 K, and a spectroscopically undetected G main-sequence secondary star. The dominant pulsating side of the primary star is centred on the L1 point. We have modelled the spectral energy distribution combined with radial velocities, and independently the TESS light curve combined with radial velocities. Both of these give excellent agreement and robust system parameters for both stars. The δ Sct star is an oblique pulsator with at least four low radial overtone (probably) f modes with the pulsation axis coinciding with the tidal axis of the star, the line of apsides. Preliminary theoretical modelling indicates that the modes must produce much larger flux perturbations near the L1 point, although this is difficult to understand because the pulsating star does not come near to filling its Roche lobe. More detailed models of distorted pulsating stars should be developed. These newly discovered single-sided pulsators offer new opportunities for astrophysical inference from stars that are oblique pulsators in close binary stars.